Neonatal screening: 9% of children with filter paper thyroid-stimulating hormone levels between 5 and 10 µIU/mL have congenital hypothyroidism - Flávia C. Christensen-Adad; Carolina T. Mendes-dos-Santos; Maura M.F. Goto; Letícia E. Sewaybricker; Lília F.R. D'Souza-Li; Gil Guerra-Junior; André M. Morcillo; Sofia Helena V. Lemos-Marini (Jornal de Pediatria)
Abstract Objectives: To determine the prevalence of congenital hypothyroidism in children with filter-paper blood-spot TSH (b-TSH) between 5 and 10 µIU/mL in the neonatal screening. Methods: This was a retrospective study including children screened from 2003 to 2010, with b-TSH levels between 5 and 10 µIU/mL, who were followed-up during the first two years of life when there was no serum TSH normalization. The diagnosis of congenital hypothyroidism was defined as serum TSH ≥10 µIU/mL and start of levothyroxine treatment up to 2 years of age. Results: Of the 380,741 live births, 3713 (1.04%) had filter paper TSH levels between 5 and 10 µIU/mL and, of these, 339 (9.13%) had congenital hypothyroidism. Of these, 76.11% of the cases were diagnosed in the first three months of life and 7.96% between 1 and 2 years of age. Conclusion: The study showed that 9.13% of the children with b-TSH levels between 5 and 10 µIU/mL developed hypothyroidism and that in approximately one-quarter of them, the diagnosis was confirmed only after the third month of life. Based on these findings, the authors suggest the use of a 5 µIU/mL cutoff for b-TSH levels and long-term follow-up of infants whose serum TSH has not normalized to rule out congenital hypothyroidism.